2020
DOI: 10.1038/s41598-020-60204-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolved Fusarium oxysporum laccase expressed in Saccharomyces cerevisiae

Abstract: Fusarium oxysporum laccase was functionally expressed in Saccharomyces cerevisiae and engineered towards higher expression levels and higher reactivity towards 2,6-dimethoxyphenol, that could be used as a mediator for lignin modification. A combination of classical culture optimization and protein engineering led to around 30 times higher activity in the culture supernatant. The winner mutant exhibited three times lower Km, four times higher kcat and ten times higher catalytic efficiency than the parental enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…To date, LAC remains the only candidate enzyme identified and functionally characterized from a coal-degrading fungus. Thus, heterologous expression of a Fusarium oxysporum LAC in the yeast Pichia pastoris was shown to depolymerize and liquefy solubilized brown coal with the release of humic and fulvic acids [58,59].…”
Section: Coal Bio-liquefactionmentioning
confidence: 99%
“…To date, LAC remains the only candidate enzyme identified and functionally characterized from a coal-degrading fungus. Thus, heterologous expression of a Fusarium oxysporum LAC in the yeast Pichia pastoris was shown to depolymerize and liquefy solubilized brown coal with the release of humic and fulvic acids [58,59].…”
Section: Coal Bio-liquefactionmentioning
confidence: 99%
“…Laccases are belonging to oxidoreductases that catalyze the O 2 reduction to H 2 O with simultaneous organic substrates oxidation. They oxidize phenolic substrates but are also able to oxidize bigger or non-phenolic substrates by LMS (laccase-mediator system), where a small phenolic compound acts as a mediator [164]. Additionally, they have been reported as potential lignin-degrading enzymes and as solubilizing agents [165,166].…”
Section: Laccasesmentioning
confidence: 99%
“…Kwiatos et al, expressed F. oxysporum Gr2 laccase in Saccharomyces cerevisiae and engineered it for getting higher effect against 2,6-dimethoxyphenol and higher expression levels. The resulted laccase had a promising potential for different industrial uses such as solubilization of brown coal, which is a clean coal technology, aiming at converting lignite to its cleaner form [164]. In 2018, Kwiatos et al, reported that F. oxysporum LOCK-1134 isolated from brown coal, efficiently bio-solubilized lignite, producing liquefied products that had over 99% less Hg and 50% less sulfur than the crude coal.…”
Section: Laccasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal mining not only visibly disrupts the aesthetics of a landscape but also disrupts all of the soil components including soil horizons, structure, microorganisms and nutrient cycles that are crucial to sustaining a healthy ecosystem [9,10]. While a number of fungi show potential as rehabilitation biocatalysts and degrade coal into a soil-like humic-rich material [11][12][13][14][15][16][17][18], the only candidate enzymes identified and functionally characterised from coal-degrading fungi so far are laccase and esterase. Heterologous expression of Fusarium oxysporum laccase in Pichia pastoris was shown to depolymerise and liquefy solubilised brown coal with the release of humic and fulvic acids [18].…”
Section: Introductionmentioning
confidence: 99%